Executive Committee Minutes 2013-03-14 - Academic Senate:::::::::
Agenda approved. Minutes delayed. Correspondence received. FSAC SETE Task Force Recommendations. Vice President of Administration and Finance Report. Discussion of recent hate graffiti incidents. Associated Students Report. FSAC Report. SAC Report. APC Report. Vice Chair Report. Chair Report. Senate agenda approved.